Digital Transformation In Islamic Banking: A Systematic Literature Review Of Opportunities, Challenges, And Research Agendas - Ella Annissa; Ismail Nura (Journal of Creative Power and Ambition (JCPA), 2026)
Digital transformation has fundamentally altered the landscape of Islamic banking, presenting both opportunities and frictions not encountered by conventional financial institutions. This article presents a systematic literature review of 18 academic articles and policy reports published between 2013 and 2025, encompassing quantitative empirical, bibliometric, and conceptual studies, as well as analyses of regulatory policies. Through thematic synthesis, five recurring thematic clusters were identified: (1) efficiency and operational performance, (2) financial inclusion via digital channels, (3) the alignment of innovation with *Maqashid al-Shari'ah* and Shari'ah governance, (4) customer adoption and technology acceptance, and (5) implementation risks and challenges specifically cyber risk and Shari'ah non-compliance. Additionally, several research gaps were identified: a scarcity of cross-jurisdictional comparative studies, a lack of mature empirical instruments for assessing digital-Shari'ah alignment, and a dominance of qualitative-descriptive methodologies that has not yet been balanced by longitudinal or mixed-method designs. These findings offer a roadmap for regulators, Islamic banking practitioners, and academics to develop a research agenda that is more focused and responsive to the accelerating digitalization of the Islamic financial sector.